PENYELESAIAN SENGKETA WANPRESTASI PADA PERJANJIAN MODAL KERJA AKIBAT MENINGGALNYA DEBITUR DITINJAU DARI PERSPEKTIF HUKUM PERDATA - Nurlaylia Hakim; Sri Wahyuni; Diana Fitriana (Truth de Journal, 2026)
Default in a working capital credit agreement may create legal disputes, particularly when the debtor  passes away before fulfilling all obligations under the agreement. Such circumstances raise legal  questions concerning the settlement of unpaid debts and the liability of heirs toward the deceased  debtor’s obligations. This study aims to analyze the settlement of default disputes in working capital credit agreements when the debtor has died and to examine whether heirs may refuse to pay the  remaining debt from the perspective of Indonesian civil law. This research employs a normative  juridical method using statutory and case approaches. The legal materials consist of primary,  secondary, and tertiary legal sources, which are analyzed qualitatively. The findings indicate that the  death of a debtor does not extinguish debt obligations. Pursuant to Article 833 paragraph (1) of the  Indonesian Civil Code, the rights and obligations of the deceased are transferred to the heirs upon  death. However, heirs are granted legal options under the Civil Code, namely accepting the inheritance  unconditionally, accepting it with the benefit of inventory, or rejecting it entirely. Consequently, the  liability of heirs for the deceased debtor’s debt depends on their legal position regarding the inheritance. The study concludes that dispute resolution must balance the creditor’s right to repayment  with legal protection for heirs in accordance with the principles of justice and legal certainty.